A novel C-type lectin with microbiostatic and immune regulatory functions from Litopenaeus vannamei. Issue 93 (October 2019) - Luo, Mengting; Yang, Linwei; Wang, Zi-ang; Zuo, Hongliang; Weng, Shaoping; He, Jianguo; Xu, Xiaopeng
Abstract: C-type lectins (CTLs) are a group of lectins with at least one carbohydrate recognition domain (CRD), the binding of which to carbohydrates requires the presence of calcium ions. CTLs generally function as pattern recognition receptors (PRRs), essentially participating in innate immunity. In the current study, a novel CTL termed LvCTL5 was identified from Pacific white shrimp Litopenaeus vannamei, which shared sequence identities with other crustacean CTLs. LvCTL5 was highly expressed in hepatopancreas and could be activated by infection with bacteria, virus and fungi. The recombinant LvCTL5 protein purified from E. coli showed microbiostatic and agglutination activities against bacteria and fungi in vitro . Silencing of LvCTL5 in vivo could significantly affect expression of a series of immune effector genes and down-regulate the phagocytic activity of hemocytes. Compared with controls, the LvCTL5-silenced shrimp were highly susceptible to Vibrio parahaemolyticus and white spot syndrome virus (WSSV) infections. These suggest that LvCTL5 has microbiostatic and immune regulatory activities and is implicated in antiviral and antibacterial responses. Highlights: Identification of a novel C-type lectin gene (LvCTL5) from Litopenaeus vannamei. LvCTL5 protein has microbiostatic and immune regulatory functions. LvCTL5 is involved in antibacterial and antiviral responses.